Evolution of the chemical industry in Brazil-Performance analysis of the Petrochemical Pole of Triunfo A evolução da indústria química no Brasil - Análise do desempenho do Pólo Petroquímico de Triunfo - Moisés Pais dos Santos; Marcia Regina Gabardo Camara (Semina: Ciências Sociais e Humanas, 1998)
The purpose of this paper is to carry out a study on evaluation in Drawing and Geometry, based on an experience developed in the State University of Londrina, with results obtained from two groups of students from Geometric Drawing and Descriptive Geometry as well as Technical Drawing. A study on evaluation was initially carried out. After that, a critical report of the developed experience was made, which allowed us to identify possible failures and difficulties. A research among the students of these two disciplines was also performed in order to confirm the positive and negative aspects of the experience. A questionnaire was answered by the students, as well. Based on studies about evaluation and the analysis of the students' reports, it was possible to plan an evaluation proposal. A proposta deste trabalho é realizar um estudo sobre avaliação em Desenho e Geometria. O objetivo é apresentar uma proposta fundamentada em uma experiência desenvolvida com alunos da Universidade Estadual de Londrina, com alguns resultados obtidos com dois grupos de alunos das Disciplinas Desenho Geométrico e Geometria Descritiva e Desenho Técnico. Inicialmente foi realizado um estudo sobre avaliação, em um segundo momento realizou-se um relato critico da experiência desenvolvida, que possibilitou levantar-se possíveis falhas e dificuldades. Para confirmar os aspectos positivos e negativos da experiência, foi realizada uma pesquisa com os alunos dessas duas disciplinas. A metodologia empregada na pesquisa foi a aplicação de um questionário. A partir dos estudos feitos sobre avaliação e da análise dos depoimentos dos alunos, foi possível delinear uma proposta de avaliação.